2003
DOI: 10.1183/09031936.03.00039203
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy after human lung transplantation

Abstract: numbers of lung transplantation (LTx) were performed with or without induction therapy with antilymphocyte antibodies, monoclonal anti-CD3 antibody or anti-interleukin-2-receptor monoclonal antibodies. It remains to be established if induction therapy after LTx is beneficial or deleterious for long-term graft and patient survival.The vast majority of lung transplant recipients receive a triple-drug maintenance regimen including a calcineurin inhibitor, a cell-cycle inhibitor and steroids. Equal proportions rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 117 publications
0
47
1
Order By: Relevance
“…Consequently, treatments have primarily focused on augmented T-cell-based immunosuppression, such as changes in calcineurin inhibitor or the addition of antithymocyte globulin (ATG) (7,8). Despite these therapies, rates of rejection and BOS remain high, and alternative treatments are desperately needed to improve overall posttransplant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, treatments have primarily focused on augmented T-cell-based immunosuppression, such as changes in calcineurin inhibitor or the addition of antithymocyte globulin (ATG) (7,8). Despite these therapies, rates of rejection and BOS remain high, and alternative treatments are desperately needed to improve overall posttransplant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that the frequency of Treg cells in peripheral blood was positively correlated with improved early lung function, 3 weeks and 3 months after lung transplantation. Since it is known that the frequency and severity of acute rejection episodes and CMV/non-CMV infection episodes following pulmonary transplantation are correlated with the later development of BOS [2][3][4], an early regulatory phenotype, enabling better lung function parameters and rendering acute rejection less likely, could potentially predict a favorable long-term outcome. The severity of ischemia-reperfusion injury, which may not be dependent on an adaptive immune response, can interfere with lung function parameters [13], and could act as a confounding variable in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, acute and chronic rejection episodes limit the midand long-term survival. The frequency and severity of acute rejection episodes and cytomegalovirus (CMV)/non-CMV infection episodes are associated with an increased risk of chronic rejection, which is synonymous with bronchiolitis obliterans syndrome (BOS) [2,3,4]. BOS is defined as an irreversible obstruction of the small airways and is routinely diagnosed and monitored with pulmonary function testing [4].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, prevention of graft rejection requires intensive, prolonged immunosuppression with corticosteroids, calcineurin antagonists, antimetabolites, and immune modulators (21). This approach, which is focused on the inflammatory component, has clear limitations, with significantly increased risks of opportunistic infection and a limited effect on angiogenesis.…”
Section: The Potential Role Of CXC Chemokines In Angiofibroproliferatmentioning
confidence: 99%